The Compliance with the Resolutory Condition as a Causal Valid of Extinction in the Work Contracts with an Indefinite Term: Temporary Indefinite Contracts? - Cjuro Vera, Cinthia Mirella (2015)
In this article, the author analyses whether Peruvian labor law permit the incorporation of a resolutive condition in undetermined contracts of employment. To do so, the author annotates a particular case of Peru, as well as some judgments of the Spanish Court of Justice.